2002
DOI: 10.1080/026404102320183176
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of video feedback for learning the golf swing

Abstract: This study was designed to examine the efficacy of video instruction relative to that of verbal and self-guided instruction. Before training, 30 golfers were assigned at random to one of three groups: video, verbal or self-guided instruction. Video instruction was defined as a practice session in which the teacher was aided by the use of video. Verbal instruction was defined as practising with the teacher providing verbal feedback. Self-guided practice was defined as practising without the aid of a teacher. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 5 publications
6
84
0
15
Order By: Relevance
“…Bertram et al (1969) also reported that video feedback did not significantly improve clubhead velocity, rather that novices significantly improved with verbal feedback whereas skilled golfers improved via self-guided practice. In contrast, two studies involving novice and mid-handicap golfers, respectively demonstrated that video or video and verbal feedback significantly improved driving distance more so than verbal or self-guided practice (Guadagnoli, et al, 2002;Guadagnoli, et al, 2001). …”
Section: Video Feedbackmentioning
confidence: 99%
See 3 more Smart Citations
“…Bertram et al (1969) also reported that video feedback did not significantly improve clubhead velocity, rather that novices significantly improved with verbal feedback whereas skilled golfers improved via self-guided practice. In contrast, two studies involving novice and mid-handicap golfers, respectively demonstrated that video or video and verbal feedback significantly improved driving distance more so than verbal or self-guided practice (Guadagnoli, et al, 2002;Guadagnoli, et al, 2001). …”
Section: Video Feedbackmentioning
confidence: 99%
“…Although Guadagnoli et al (2002) found that mid-handicappers who were given video or video and verbal feedback significantly increased their driving distance two weeks post acquisition, they suffered small decrements in performance at retention 1 (two days post-acquisition). While these results are somewhat mixed, they do suggest that unskilled to moderately skilled golfers can increase driving distance from video feedback, but such improvements may take a number of weeks to occur and may initially involve a small deterioration in performance.…”
Section: Video Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Taylor's study (Taylor, 2006) about the foot fakes in football with 8th-grade students did not find a significant difference between the group which received the visual feedback through video and the group that received the verbal feedback. Furthermore, the study performed on golfers by (Guadagnoli, Holcomb, & Davis, 2002). revealed that the groups to which verbal and visual feedbacks were provided were less successful than the control group.…”
Section: Introductionmentioning
confidence: 99%